2017
DOI: 10.5539/jas.v9n5p54
|View full text |Cite
|
Sign up to set email alerts
|

Social Behavior and Productive and Stress Parameters in Holstein Steers Fattened in Three Contrasting Production Systems

Abstract: Beef production with Holstein male calves is becoming more intensive in Uruguay. Some of the new systems with confined animals could improve productivity but also could compromise animal welfare. The aim of this study was to compare animal welfare, stress evidence and productivity of castrated young males reared in three different productive systems. The traditional pastoral system (T3) was compared with, a confined fattening system (T1) and an alternative one with confinement and six hours diary access to pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Pushing behavior was more observed in animals transported over long distances. Hypothetically, this could be explained by the fact that animals transported over long distances arrived more exhausted at the slaughterhouse, performing behaviors that demand less energy, such as pushing other animals to moving them away, instead of head-butting to promote this action ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pushing behavior was more observed in animals transported over long distances. Hypothetically, this could be explained by the fact that animals transported over long distances arrived more exhausted at the slaughterhouse, performing behaviors that demand less energy, such as pushing other animals to moving them away, instead of head-butting to promote this action ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining feedlot housed cattle observed that cattle in feedlots engaged in agonistic behaviors more frequently and for longer durations (e.g., headbutting, pushing, displacement) [19] compared to cattle with access to pasture. Similarly, feedlot-housed cattle spent more time standing and walking, as well as engaged in lying for a shorter duration of time paralleled to cattle housed in a hoop barn [18].…”
Section: Summary Of Main Findingsmentioning
confidence: 99%